Gone With the Covid – Scarlet in Quarantine: An Interview with Sarah Combs - Sarah Combs; Emmeline Gros (Transatlantica)
Artist Sarah Combs (https://sarahelizabethcombs.com/) claims that art and laughter have the power to give us some respite from our fears and worries. Laughter can be just the right medicine to forget our troubles. As a family Covid-19 quarantine project, Combs recently created a short film, Gone With the Covid, a spoof of the classic film, Gone With the Wind. Beyond laughter and comic relief, is parody also a conduit of critique, or are certain topics—racism, the legacy of slavery, racial inequalities in epidemics like Covid-19—too serious issues to be parodied? In this interview, Sarah Combs explains her motivations and the challenges she had to face in the process.